A Tailorable Spray‐Assembly Strategy of Silver Nanowires‐Bundle Mesh for Transferable High‐Performance Transparent Conductor. (24th September 2020) - Xiong, Jiaqing; Li, Shaohui; Ciou, Jing‐Hao; Chen, Jingwei; Gao, Dace; Wang, Jiangxin; Lee, Pooi See
Abstract: Achieving a well tradeoff between electrical and optical performances remains challenging for conventional silver nanowires (AgNWs) random network conductors. An innovative AgNW‐bundle mesh (AgBM) composed of exquisite knots and abundant open area is realized by one‐step spray‐assembly at room temperature, showing high optoelectronic performance. A dynamic assembly mechanism based on the spray assembly of isopropanol‐based AgNWs ink is revealed, ensuring a favorable coffee‐ring effect dominated by the capillary flow rather than Marangoni reflux, driving the AgNWs to deposit at the edges of droplets. The initially formed AgNW‐bundle rings serve as template to constrain the movement of AgNWs from the subsequent droplets, rendering scalable and continuous accumulation of nanowires to produce a connective AgBM. The controlling factors of surface tension of substrates and ink, wettability, spreading and pinning effect of the ink droplets, as well as tunable assembly driving force determined by spraying rate are revealed, realizing an universal spray‐assembly strategy for tailorable fabrication of AgBMs using AgNWs with different sizes in diameter (20–120 nm) and length (20–200 µm). Thicker AgBMs could reduce the sheet resistance without severe sacrifice of transparency. Thinner AgNW‐bundles/knots with better electrical connection can be realized from the finer and longer AgNWs, delivering higher optoelectronic performance. Abstract : A dynamic spray‐assembly mechanism of silver nanowires‐bundle mesh (AgBM) is revealed, indicating pinned ink‐droplets with a favorable coffee‐ring effect is important for the scalable and continuous accumulation of nanowires at the edges of droplets, producing a connective AgBM for high‐performance flexible transparent conductor. Surface tension, wettability, and spraying rate are controllable for a tailorable spray‐assembly strategy universal for various AgNWs.